The bizarre body - Kenah, Katharine (Columbus, OH : Waterbird Books, 2005)
Examines some of the interesting facts about the human body such as the strongest muscles in the body, the number of nerve cells in the brain, a baby's heartbeat, and how fast fingernails and toenails grow.
2.9
K-3
Keywords: Human body -- Juvenile literature; Human anatomy -- Juvenile literature; Human body; Human anatomy; Human body; Human anatomy